Transforming Leadership Style: Enhancing Organizational Culture, Innovative Behavior and Employees Performance - Nilasari, B Medina; Nisfiannoor, Muhammad; Pongoh, Andri Sebastian (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study aimed to investigate how positive Employees Performance can be achieved when leadership behavior fosters Organizational Culture and Employees Innovative Behavior.Design/Methodology/Approach: This quantitative study obtained data through an online questionnaire, where responses were collected from 150 employees of private companies in DKI Jakarta area. The data were then analyzed using Structural Equation Model (SEM) with AMOS version 25.Research findings: The results showed that Transformational Leadership had no direct effect on Organizational Culture, Employees Innovative Behavior, or Employees Performance. However, Transactional Leadership had a direct effect on Organizational Culture and Employees Innovative Behavior, but not on Performance. Even when mediated by Organizational Culture and Innovative Behavior, Transformational Leadership still had no effect on Performance. On the other hand, Transactional Leadership, when mediated by Organizational Culture and Employees Innovative Behavior, had more significant influence on Performance.Theoretical Contribution/Originality: This study offered a novel perspective by showing that neither Transformational nor Transactional Leadership had a direct impact on Employees Performance. However, the mediating role of Organizational Culture and Innovative Behavior strengthened the influence of Leadership on Employees Performance.Practitioners/Policy Implications: To improve Employees Performance through Transactional Leadership, leaders should cultivate innovative Organizational Culture and foster Employees Innovative Behavior. In addition, leaders should address deviations in employees behavior and recognize positive contributions, ranging from verbal praise to offering promotion opportunities.Research Limitations/Implications: This study focused on Transformational Leadership, Transactional Leadership, Organizational Culture and Employees Innovative Behavior, as well as Employees Performance. Future studies were recommended to consider adding independent variables such as Creative Self-efficacy and Humble Leadership. Meanwhile, companies were expected to maintain a flexible culture to adapt to changes, and continuously nurture employees' creative ideas by providing opportunities. Leaders should also consistently monitor employees behavior and acknowledge good performance.